Deep Brain Stimulation and Treatment Outcomes of Young- and Late-Onset (≤55 Years) Parkinson's Disease: A Population-Based Study - Camerucci, Emanuele; Stang, Cole D.; Turcano, Pierpaolo; Tipton, Philip W.; Bower, James H.; Hassan, Anhar; Klassen, Bryan T.; Savica, Rodolfo (Frontiers in Neurology, 2021)
Background: No studies have reported the rate of motor complications (MC) and response to medical and surgical treatment in a population-based cohort of young-onset Parkinson’s Disease (YOPD) patients and a cohort of sex-matched late-onset Parkinson’s Disease (LOPD). Objective: To assess the outcomes of dopaminergic treatment in YOPD and LOPD, explore treatment-induced MC, medical adjustment, and rate of deep brain stimulation (DBS). Methods: We used the expanded Rochester Epidemiology Project (eREP) to investigate a population-based cohort of YOPD between 2010-2015 in 7 counties in Minnesota. Cases with onset ≤55 years of age were included as YOPD. An additional sex-matched cohort of LOPD (onset at ≥56 years of age) was included for comparison. All medical records were reviewed to confirm the diagnoses. Results: In the seven counties 2010-15, there were 28 YOPD patients, which were matched with a LOPD cohort. Sixteen (57%) YOPD had MC, as compared to 9 (32%) LOPD. In YOPD, 9 had motor fluctuations (MF) and Levodopa-induced dyskinesia (LID) together, whereas 3 had LID only and 4 MF only. In LOPD, 3 had MF and LID, 3 MF only, and 3 LID only. Following medical treatment for MC, 6/16 YOPD (38%) and 3/9 (33%) LOPD had symptoms resolution. In YOPD, 11/16 (69%) were considered for DBS implantation, in LOPD they were 2/9 (22%), but only 7 (6 YOPD and 1 LOPD) underwent the procedure. YOPD had significantly higher rates in both DBS candidacy and DBS surgery (respectively, p= 0.03 and p= 0.04). Among DBS-YOPD, 5/6 (83%) had positive motor response to the surgery; the LOPD case had a poor response. We report the population-based incidence of both YOPD with motor complications and YOPD undergoing DBS, which were 1.17 and 0.44 cases per 100,000 person-years, respectively. Conclusion: Fifty-seven percent of our YOPD patients and 32% of the LOPD had motor complications. Roughly half of both YOPD and LOPD were treatment resistant. YOPD had higher rates of DBS candidacy and surgery. Six YOPD and 1 LOPD underwent DBS implantation and most of them had a positive motor response after the surgery.